(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines the integration of gamification techniques into language teaching as a means of enhancing student engagement, motivation, and learning outcomes. Gamification, defined as the application of game-design elements and game principles in non-game contexts, has emerged as a powerful pedagogical strategy in foreign language education. The study explores the theoretical foundations of gamification, including self-determination theory and flow theory, and analyzes practical implementations of game elements such as points, badges, leaderboards, narratives, quests, and rewards in English language classrooms. The article also discusses the role of digital platforms (Kahoot, Quizlet, Duolingo, Classcraft) and considers both the benefits and challenges of gamified instruction. Findings indicate that well-designed gamification significantly increases learner motivation, classroom participation, vocabulary retention, and willingness to communicate in the target language. The article concludes with practical recommendations for English teachers seeking to implement gamification meaningfully and sustainably in their classrooms.